Privacy Preserving Public Auditing and Recovery Using Backup & Restore Method for Secure Cloud Storage (International Journal of Engineering and Computer Science, 2015)
As cloud computing provides many relinquish characteristics to users like on demand self-service, storage, multi-tenancy, pay-as-you go and access information from shared pool of configurable computing resources without any burden. So that users stores their data remotely anywhere and enjoy on demand services of cloud. Cloud computing is capable of handling mass data storage and intense computing tasks so that, user can store huge amount of data on cloud without any storage capacity limitations. Despite this, users no longer have a physical possession of the outsourced data which make data integrity and availability in cloud a dreadful task, for those which has limited computing resources. Besides also, user can use cloud storage as it is local without any worry for its integrity check. Thus, to avoid this burden from user so there is need of public auditing for cloud storage. So users can rely on third party auditing (TPA) to check its outsourced data integrity. TPA should effectively do its auditing process without any risk towards user data privacy and provide no additional online burden to user. In this paper, we propose secure cloud storage system which will maintain outsourced data confidentiality and integrity by supporting privacy preserving public auditing. We further extend our system to provide recovery of lost data and also identify which block is lost from which file and recovery of that block or file to maintain data availability in cloud server.